Influence of biofeedback weight bearing training in sit to stand to sit and the limits of stability on stroke patients - Yang, Dae Jung (J Phys Ther Sci, 2016)
[Purpose] The purpose of this study is to observe the influence of biofeedback weight bearing training in sit to stand to sit and limits of stability on stroke patients. [Subjects and Methods] For subjects of this study, 30 stroke patients were randomly divided into two groups of 15, a biofeedback weight bearing training group and a functional weight bearing training group. Biofeedback weight bearing training was conducted for 30 minutes, five times a week for eight weeks, using Biorescue. Analysis of sit to stand to sit was done with LUKOtronic while the analysis of limits of stability was done with Biorescue. [Results] In a comparison of sit to stand to sit and limits of stability between the two groups before and after intervention, Group I showed significant difference in sit to stand to sit and limits of stability when compared to Group II. [Conclusion] This study concludes that biofeedback weight bearing training is more effective in improving sit to stand to sit and limits of stability in stroke patients.